Moral versus Commercial Economies: Transylvanian Stories - Velicu, Irina (New Political Science, 2014)
Historically, the production of a market society has depended on the commodification of valuables such as land and labour, which has also meant the disembedding of capital from elements of the “primordial,” such as kinship, spiritual relations, and identities. Today we are still witnessing the invocation of such elements of moral economies as a basis for people's collective mobilization against market pressures. The case study in this article refers to Rosia Montana, a semi-urban village in Transylvania where a Canadian corporation is planning to create the largest cyanide opencast mine in Europe. Through attempts at privatizing and commodifying whole areas of social life, the market logic promoted by the corporation in the last twelve years portrays the mine as the “only alternative” for the development of the region. Rosieni and activists have blocked the project for more than fourteen years by reclaiming other fundamental values related to spirituality, ancestry, land, and nature. They challenge the prevailing violence of the market by problematizing the logic of the commercial economy and by re-evaluating what the corporate project devalues. How does the post-communist context inspire a moral critique of global corporate capitalism and a democratic socialist alternative? In this article Polanyi's argument related to the “fictitious commodities” of the market will be used to support the argument that moral principles inspire forms of resistance against commodification in the former Eastern bloc and may produce future alternative forms of development. If one noticed an increase in social and environmental activism in Romania over the last five years would it also be due to the perseverance of Rosieni and its supporters in challenging not only a corporation and some co-opted/corrupted officials, but an entire dominant discourse of neoliberalism?
Keywords: Canadian corporations; Rosia Montana; Transylvania (Romania); commodification; corporate capitalism; disembeddedness; economic aspects; moral economy; neoliberalism